Republic of Belarus : Ex Post Evaluation of Exceptional Access Under the 2009 Stand-By Arrangement. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
Belarus was hard hit by the global economic crisis. An exceptional access Stand-By Arrangement (SBA) was, therefore, agreed in early 2009. The program was generally successful and most program conditions were met. The program was overall well designed, but with some shortcomings. While in part owing to external shocks, those problems experienced under the program also reflected rapid directed lending. Lessons from the review are many, the main one is the criticality of incorporating fully ownership, including at the highest levels, in program design and conditionality.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet